The role of the public organizations as a manager of school pupils tourism. The example of the society ,,Nasze Szwederowo” - Parzych, Krzysztof; Tatysiuk, Natalia; Gotowski, Rafał (Journal of Education, Health and Sport, 2017)
Tourism of children and youth is an interesting issue both as a social phenomenon and as an object of many different scientific disciplines. The subject of the study was an analysis of the role of public benefit organizations in the context of resting youths in school. As a case study, we used the example of the "Our Szwedowo" Society, which has been organizing leisure activities for school children in northern Poland for many years. An analysis of the organizational activities of the company and the characteristics of tourist and leisure trips organized by them in the years 2012-2017 were analyzed. The results indicate that "Our Union" is an organization with a regional impact covering the central part of Poland. The activity of the society is aimed at organizing children's and youth's holiday, especially summer camps and wintering for children from poor and disadvantaged families, in close cooperation with local governments and on the basis of individual declarations of participation.